Forced emigration from Russia 2022: Russian IT-specialists’ potential for Central Asian CIS member countries - A. Kh. Rakhmonov (Вестник университета, 2023)
The article examines the factors and the scale of a forced emigration’s new wave from Russia to Central Asian countries. Wages in Central Asian countries are one of the factors in attracting highly qualified specialists from Russia. Such factors also include the potential of Russian IT-specialists in Central Asian countries and the policy of Central Asian countries to attract and retain IT-specialists from Russia. Emigration from Russia to Central Asian countries is a new wave of forced emigration. Various categories of people are leaving Russia: from ordinary emigrants to highly qualified specialists and also IT specialists. The active policy of the Central Asian countries to attract and retain specialists from Russia, as well as the visa-free regime between the Central Asian countries and Russia played a big role in choosing countries for the professionals’ migration from Russia. For the Central Asian country this is a new impetus for the development of an innovative economy. The article purpose is to identify the features of forced emigration from Russia to the Central Asian countries that are Commonwealth of Independent States’ members, as well as the prospects for using the potential of IT specialists in the development of Central Asian member countries of Commonwealth of Independent States.